Exploration of Directive Speech in the Film Dialogue "Until Tomorrow" by Evelyn Afnilia - Sandra, Sandra Gita Wardany; Erni, Erni (Jurnal Sastra Indonesia, 2025)
The problem in this study is how the function of directive speech acts in the film "Until Tomorrow" by Evelyn Afnilia. This study aims to describe and analyze the function of directive speech acts in the film "Until Tomorrow" by Evelyn Afnilia. The theory used in this study is the theory of the function of directive speech acts proposed by George Yule. This study uses a qualitative approach using the Content Analysis method. The data source in this study is all the speech of the Until Tomorrow film players. The research data includes all the speeches of the Until Tomorrow film players, which are included in the function of directive speech acts. Data were collected through listening techniques, note-taking techniques, and documentation techniques. The study's results in the film Until Tomorrow found 38 directive speech acts with seven speech act functions. These findings conclude that the most frequently occurring directive speech acts are commanding directive speech acts, consisting of 14 data points. The commanding function in this film is full of emotional pressure and conflict, such as difficult decisions or urgent responsibilities. In situations like this, characters tend to use commands to assert authority, convey urgency, or regulate actions, rather than a more polite form of asking. The dominance of the “Commanding” function shows how the emotional pressure and conflict in this film push the characters to take direct, decisive action, which is important for building the intensity of the drama in the romantic narrative.